Greater alteration of gut microbiota occurs in childhood obesity than in adulthood obesity - Yu, Zhongjia; Yu, Xiang-Fang; Zhao, Xiu; Su, Zhe; Ren, Pei-Gen (Frontiers in Pediatrics, 2023)
The children's gut microbiota, associated with the development of obesity, is in maturation. The impact of obesity on the gut microbiota in childhood could have a more significant effect than on adulthood and eventually be lifelong lasting, but it has been rarely studied. Aimed to discover the difference in gut microbiota between children and adults with obesity, we collected published amplicon sequencing data from National Center for Biotechnology Information (NCBI) and re-analyzed them using a uniform bioinformatic pipeline, as well as predicted the obesity using gut microbiota based on the random forest model. We found that the gut microbiota had a significant difference between children with and without obesity, but this did not happen in adults. Based on the random forest model, it was more challenging to predict childhood obesity using gut microbiota than adulthood obesity. Our results suggest that gut microbiota in childhood is more easily affected than in adulthood. Early intervention for childhood obesity is essential to improve children's health and lifelong gut microbiota-related health.